Impact of Posterior Quadratus Lumborum Block on Acute Pain Relief and Chronic Pain Prevention in Breast Cancer Surgery - Min Wang; Shu-Jie Niu; Jin Wu; Yi-Wei Zhong; Zi-Yun Lu; Qun Fu; Bing-Bing Li (Pain and Therapy)
Abstract Introduction Breast cancer surgery is a common surgical procedure often associated with acute and chronic postoperative pain. As part of multimodal analgesia, the erector spinae plane block (ESPB) has been shown to effectively alleviate pain after breast cancer surgery. This study is the first to apply the posterior quadratus lumborum block (posterior QLB) for perioperative analgesia in breast cancer surgery. The aim of this research was to evaluate whether ESPB and QLB2 can relieve acute and chronic pain following breast cancer surgery. Methods A total of 120 female patients undergoing breast cancer surgery were randomly assigned to receive either ESPB, posterior QLB, or no intervention. All patients were administered sufentanil patient-controlled intravenous analgesia postoperatively. The primary outcome was the visual analog scale (VAS) pain scores recorded at 2, 6, 18, 24, and 48 h post-surgery under rest and motion conditions. Secondary outcomes included the incidence of moderate-to-severe pain within 24 and 48 h post-surgery, intraoperative fentanyl cumulative dosage, postoperative rescue analgesia, chronic pain incidence, recovery quality of life, and adverse events. Results Compared to the group receiving conventional treatment (group C), the incidence of moderate-to-severe pain within 24 h post-surgery was significantly lower in both the group receiving ESPB (group E; 16.7% vs. 46.2%, P < 0.05) and the group receiving QLB (group Q; 20.5% vs. 46.2%, P < 0.05). Additionally, the proportion of patients requiring rescue analgesia was significantly reduced in both group E and group Q, compared to group C (group C vs. E vs. Q: 30.8% vs. 7.1% vs. 10.3%, P = 0.007; group C vs Q: 30.8% vs. 10.3%, P = 0.025; group C vs. E: 30.8% vs 7.1%, P = 0.006; group Q vs. E: 10.3% vs. 7.1%, P = 0.141). At 3 months post-surgery, group Q had a significantly lower incidence of chronic pain compared to both group C (19.5% vs. 71.8%, P < 0.05) and group E (19.5% vs. 57.1%, P < 0.05). No significant differences were observed between the groups in terms of VAS scores at 2, 6, 18, 24, or 48 h, intraoperative fentanyl consumption, postoperative nausea and vomiting, time to first mobilization, time to first oral intake, the length of hospital stay, or Quality of Recovery—15 Items (QoR-15) scores at 3 months post-surgery (all P > 0.05). Conclusion Compared with conventional intravenous analgesia, the combination of ultrasound-guided ESPB and posterior QLB significantly reduces the incidence of moderate-to-severe pain and the need for rescue analgesia within 24 h post-surgery. Furthermore, a single posterior QLB significantly reduces the incidence of chronic pain at 3 months post-surgery in patients with breast cancer. Trial registration Clinical trial number: ChiCTR2000041471.